Omega and related polynomials of polyomino chains of 4 k-cycles - ALAEIYAN, MEHDI; GILANI, ALIREZA; MOJARAD, RASOUL; ASADPOUR, JAFAR (Kuwait Journal of Science, 2014)
Omega polynomial of a graph G is defined, on the ground of "opposite edge strips" ops: where is the number of ops strips of length . The Sadhana polynomial can also be calculated by ops counting. In this paper we compute these polynomials for polyomino chains of 4 -cycles. Also by using Omega polynomial we can compute the (edge) PI polynomial for this graph.